Analysis of Productivity and Annual Cost of Casting Plates and Beams Using Concrete Pump and Columns with Concrete Bucket (Case Study of Residence Apartment Project) - Kustanrika, Irma Wirantina; Purwanto, Wawan; Sofyan, Muhammad; Sari, Yetti Anita; Wahyuningtias, Asri (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
Traditional casting in multi-storey buildings necessitates specialized equipment such as concrete buckets and concrete pumps for the application of ready mix concrete. Various types of equipment have an impact on both productivity and the duration of casting. This study collected primary data by conducting field observations at the B Residence Apartment Project, with a specific focus on worker and equipment needs, tool effectiveness, and labor force. The secondary data comprised of structural photos and cost information pertaining to manpower and equipment. The study revealed that the utilization of a concrete pump incurs a cost of IDR 1,231,543 m³, but employing a concrete bucket results in a cost of IDR 1,719,141 m³. The concrete pump achieved a volume of 281.02 m³ in a duration of 1101 minutes, while the bucket achieved a volume of 47.98 m³ in a duration of 538.77 minutes. The productivity of the concrete pump was 0.255 m³/minute, whereas the productivity of the concrete bucket was 0.089 m³/minute. According to these findings, utilizing the concrete pump will greatly enhance time efficiency and decrease the incurred expenses.